2017
DOI: 10.1039/c6cc09392b
|View full text |Cite
|
Sign up to set email alerts
|

Microscale coiling in bis-imidazolium supramolecular hydrogel fibres induced by the release of a cationic serine protease inhibitor

Abstract: Gels formed by a gemini dicationic amphiphile incorporate a serine protease inhibitor, which could be used in a new approach to the treatment of Rosacea, within the fibres as well as in the space between them, affecting a number of gel properties but most importantly inducing remarkable fibre coiling at the microscopic level as a result of drug release from the gel. Drug release and skin permeation experiments show its potential for topical administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…Permeation experiments were performed ex vivo to assess the permeation of ketorolac across human skin as well as across vaginal mucosa according to previously reported methodologies [ 9 , 20 , 21 ], in both cases under an infinite-dose regimen [ 22 ]. The cumulative amount of ketorolac permeated through each tissue along time is shown in Figure 5 A, and the permeation parameters calculated can be seen in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Permeation experiments were performed ex vivo to assess the permeation of ketorolac across human skin as well as across vaginal mucosa according to previously reported methodologies [ 9 , 20 , 21 ], in both cases under an infinite-dose regimen [ 22 ]. The cumulative amount of ketorolac permeated through each tissue along time is shown in Figure 5 A, and the permeation parameters calculated can be seen in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The supramolecular hydrogels formed upon mixing bis‐imidazolium amphiphile 1⋅2 Br with water and ethanol were strongly influenced by both neutral and cationic drugs, whereas previous work involved studying the incorporation of anionic drugs and very recently the incorporation of a cationic drug was studied; these hydrogels were studied for the treatment of rosacea. The type of drug strongly influenced the nanometric structure of the gel fibers, and importantly, NMR spectroscopy indicated that the drugs not only remained dissolved at the interstitial space of the gel (as indicated by SEM) but that up to 0.84 moles of drug per mole of gelator were incorporated within the fibers.…”
Section: Discussionmentioning
confidence: 99%
“…1) that self-assembles into supramolecular nanobres leading ultimately to physical gels in mixtures of water and ethanol. 35,36 Here we focus on the initial stages of bre formation and the activation energies involved. The initial aggregation is triggered by addition of water to homogeneous ethanolic solutions of 1$2Br (that are stable up to 0.2 M at 292 K); the samples are mixed quickly with Self-assembly of nanofibres.…”
Section: Fibre Formation and Kinetic Analysismentioning
confidence: 99%